1984
DOI: 10.1139/v84-046
|View full text |Cite
|
Sign up to set email alerts
|

O—O stretching frequencies of cyclic peroxides. Stabilization of peroxides by alkoxy substituents

Abstract: The O—O stretching frequencies of some alkyl substituted 1,2-dioxacyclohexanes are near 730 cm−1 and those of some alkyl substituted 1,2-dioxetanes are in the range 670 ± 20 cm−1. Alkoxy substituents cause the frequency to increase; that for tetramethoxy-1,2-dioxetane is 752 cm−1. Alkoxy substituents appear to stabilize peroxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…LH-MS1 is a typical peroxide according to the O-O distance (1.56 Å) and O-O stretching frequency (717 cm À1 ). 83 The calculated CO stretching frequency of LH-MS1 is 1743 cm À1 , and this is in reasonable agreement with experiments. 58,78,84 2g) would be highly reversible.…”
Section: Conventional Revised Langmuir-hinshelwood Pathwaysupporting
confidence: 81%
“…LH-MS1 is a typical peroxide according to the O-O distance (1.56 Å) and O-O stretching frequency (717 cm À1 ). 83 The calculated CO stretching frequency of LH-MS1 is 1743 cm À1 , and this is in reasonable agreement with experiments. 58,78,84 2g) would be highly reversible.…”
Section: Conventional Revised Langmuir-hinshelwood Pathwaysupporting
confidence: 81%
“…The newly formed C−O bond stabilizes the reaction product and makes the formation of LH-MS slightly exothermic (ΔG = −0.09 eV) with respect to LH-IS1. In LH-MS, the O−O distance of 1.50 Å and the O−O stretching frequency of 811 cm −1 are both typical of O−O bonds in peroxides 93. The CO stretching frequency in LH-MS was calculated as 1754 cm −1 , which falls in the higher range of experimentally reported values 12,…”
mentioning
confidence: 71%
“…From a study of the vibrational spectra of 1 and its lactol derivatives, it has been concluded [18] that the peroxide linkage contained therein is characterized by a frequency at 722 cm-'. This is a plausible value since the 0-0 stretching mode is expected to lie between 600 and 900 cm-' [ 191 [20]. Moreover, this mode is usually identified by two criteria; a Raman-active component which should show as a strong polarized band, and a corresponding IR band which should be either absent or weak.…”
mentioning
confidence: 99%